Crack path for run-out specimens in fatigue tests: is it belonging to high- or very-high-cycle fatigue regime? - A. Shanyavskiy (Fracture and Structural Integrity)
Fatigue tests run-out specimens up to 106 – 5x107 load cycles are used to determine the stress level named “fatigue limit”. Nevertheless, it is not clear what kind of fatigue cracking takes or will take place in these specimens. To discuss this problem, fatigue tests of titanium alloy VT3-1 specimens have been performed under tension with different values of R-ratio and under rotating-bending after various thermo-mechanical treatments (tempering, surface hardening and their combinations). Well-known S-N curves in High-Cycle- Fatigue regime have been plotted with run-out specimens usually used for “fatigue limit” determination. Then, after fatigue tests, run-out specimens have been tensed up to their failure, and fracture surface analyses have been performed for all tested specimens. It is found that run-out specimens in all combinations of treatments, for different R-ratio, have fracture surfaces for crack path in Very-High-Cycle-Fatigue regime. Based on this result, all S-N curves have been reconstructed in duplex curves for High- and Very-High-Cycle-Fatigue regime without using knowledge about “fatigue limit”. Detailed fracture surfaces analyses have been developed, and crack paths have been compared for various combinations of materials and surface states.